Evaluation of free light chains of immunoglobulins in normal and pathological seminal fluids: Preliminary data. (30th November 2021) - Basile, Umberto; Vergani, Edoardo; Napodano, Cecilia; Bruno, Carmine; Marino, Mariapaola; Oliva, Alessandro; Gulli, Francesca; Mancini, Antonio
Abstract: Immunoglobulins free light chains (FLCs) are assayable in several biological fluids. Currently, there are no reports on FLCs in seminal plasma. The aims of our study were to investigate the presence and detectability of FLCs in seminal plasma and to evaluate the usefulness of this assay in the diagnostic approach to infertile patients. We enrolled 61 patients aged 18–50 years. Semen analysis was performed. They were divided into four groups: controls–normozoospermic, 10 patients, mean ± SEM age 35 ± 1.5 years; varicoceles (VAR), 18 patients aged 24.3 ± 0.96 years; inflammatory (INF) seminal fluids, 24 patients, aged 38.8 ± 2.2 years; and varicoceles and inflammatory (VAR/INF) seminal fluids, 9 patients, aged 29.5 ± 0.71 years. A trend towards higher λ FLCs levels was evidenced in the INF and VAR/INF groups. κ FLCs were higher in normozoospermic patients with lower levels in VAR, both isolated and associated with inflammatory parameters. This differential pattern of the two types of FLCs reached statistical significance when comparing κ / λ ratio, with significant lower levels in VAR vs controls. This is the first report of FLCs assay in seminal plasma. We can hypothesize that λ FLCs are increased in inflammatory processes, whether κ FLCs seem to be influenced by other molecular mechanisms related to varicocele.